Electronic, magnetic and structural properties of Co3O4 (100) surface: a DFT+U study - Hashim, Ameerul Hazeeq; Zayed, Ala' Omar Hasan; Zain, Sharifuddin Md; Lee, Vannajan Sanghiran; Said, Suhana Mohd (Elsevier, 2018)
The three most stable (100), (110), and (111) surfaces exposed by Co 3 O 4 are effective catalysts for various oxidation reactions. Among these surfaces, (100) has not yet received ample attention. In this study, we investigated the structural, electronic and magnetic properties of Co 3 O 4 (100) surface using density functional theory calculations. By considering both stoichiometric and nonstoichiometric surface structures of the two possible terminations, A and B. Besides the greater stability of the newly proposed stoichiometric models compared to nonstoichiometric models reported in previous studies, the results show that the B termination is energetically preferred over the entire range of oxygen chemical potentials. Unlike the bulk, Co 3+ octahedral ions become magnetic at the surface, which leads to interesting surface magnetic properties. Density of states (DOS) indicate a small band gap of 1.15 eV for the B-stoichiometric model, due to the presence of surface states in the bulk band gap. More polar surface with a very narrow band gap is found in the A-nonstoichiometric model. These surface states may play an important role in the magnetism and metallicity observed experimentally in several Co 3 O 4 systems.